2022
DOI: 10.1038/s41598-022-13501-w
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pelvic floor disorders in adult women being seen in a primary care setting and associated risk factors

Abstract: Determine the prevalence of pelvic floor disorders (PFD) stratified by age, race, body mass index (BMI), and parity in adult women attending family medicine and general internal medicine clinics at an academic health system. The medical records of 25,425 adult women attending primary care clinics were queried using International Classification of Diseases-10th Revision codes (ICD-10 codes) for PFD [urinary incontinence (UI), pelvic organ prolapse (POP), and bowel dysfunction (anal incontinence (AI) and difficu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 10 publications
1
22
1
1
Order By: Relevance
“…Pelvic floor dysfunctions are very common health problems with costly treatment and have negative effects on the quality of life of millions of men and women (4)(5)(6)13) . On the other hand, with approaches protecting PFH, it is possible to prevent dysfunctions and support the treatment (14)(15)(16)(17) .…”
Section: Discussionmentioning
confidence: 99%
“…Pelvic floor dysfunctions are very common health problems with costly treatment and have negative effects on the quality of life of millions of men and women (4)(5)(6)13) . On the other hand, with approaches protecting PFH, it is possible to prevent dysfunctions and support the treatment (14)(15)(16)(17) .…”
Section: Discussionmentioning
confidence: 99%
“…It remains difficult, however, to determine the true prevalence of PFD because many women who suffer from FFD symptoms choose not to seek medical assistance and some are even reluctant to discuss PFD symptoms with their caregivers. The prevalence of PFD increases with older age and elevated body mass index [ 3 , 4 ]. Other than age and obesity, risk factors for PFD include smoking, mode of delivery, familial predisposition, race, and connective tissue disorders [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that parity was not associated with the incidence of PFDs; however, others reported that parity had an impact on the development of PFDs and affected pelvic floor muscle strength (PFMS). [14][15][16][17][18][19] further studies investigating the association between parity and pelvic floor injury are warranted. Therefore, this study aimed to evaluate the impact of parity on pelvic floor morphology and function using the modified Oxford Scale (MOS), surface electromyography (sEMG), and 3-dimensional (3D) pelvic floor ultrasonography during the postpartum period.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that parity was not associated with the incidence of PFDs; however, others reported that parity had an impact on the development of PFDs and affected pelvic floor muscle strength (PFMS). [14–19] As such, further studies investigating the association between parity and pelvic floor injury are warranted.…”
Section: Introductionmentioning
confidence: 99%